SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN PRODUK UNGGULAN DAERAH MENGGUNAKAN METODE ENTROPY DAN ELECTRE II (STUDI KASUS: DINAS KOPERASI, INDUSTRI DAN PERDAGANGAN KABUPATEN LAMONGAN) - Handoyo, Eko; Cahyani, Andharini Dwi; Yunitarini, Rika (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2014)
Competition superior product in the future become more and more stringent with the increasing pace of economic development, industrial growth and technological progress. This competition makes each industry should be more careful in formulating policy formulation stratgi. Making the decision to get a superior product that suits your needs and abilities required an accurate and effective decisions so that no one and minimize the loss in terms of cost and time. This study uses the entropy method and elactre II. Research with this method of ranking the results based on the amount of gain dominance resulted in ranking the more partial and sensitive than perangkingan based level. Criterion in this system is the turnover, labor, investment value, the target market, the amount of raw materials and the number of firms in a superior product. This study matches the accuracy of the system reaches 30%.